2021
DOI: 10.3389/fphys.2021.748517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Exercise on Liver Lipid Metabolism in Chinese Patients With NAFLD: A Systematic Review and Meta-Analysis

Abstract: Purpose: Using meta-analysis to evaluate the effect of various long-term exercises (more than 4 weeks) on liver lipid metabolism of Chinese patients with non-alcoholic fatty liver disease (NAFLD) and provides more targeted exercise recommendations.Methods: Four databases consisting of PubMed, Web of Science, China Science and Technology Journal Database (VIP), China Knowledge Resource Integrated Database (CNKI) were searched up to May 2021. Randomized controlled trials (RCTs) were eligible, and the outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…As described in the introduction, exercise decreases hepatic fat may be independent of energy consumption partially. Although many investigations have examined the effectiveness of a single exercise modality on hepatic fat reduction, few studies have compared the different combinations of resistance training plus moderate-intensity continuous training or high-intensity interval training ( 28 , 50 , 51 ). In the current physical activity guidelines, individuals with chronic diseases need to perform moderate-intensity aerobic physical activity or vigorous-intensity aerobic physical activity combined with muscle-strengthening activity.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the introduction, exercise decreases hepatic fat may be independent of energy consumption partially. Although many investigations have examined the effectiveness of a single exercise modality on hepatic fat reduction, few studies have compared the different combinations of resistance training plus moderate-intensity continuous training or high-intensity interval training ( 28 , 50 , 51 ). In the current physical activity guidelines, individuals with chronic diseases need to perform moderate-intensity aerobic physical activity or vigorous-intensity aerobic physical activity combined with muscle-strengthening activity.…”
Section: Discussionmentioning
confidence: 99%
“…Various systematic reviews with meta-analyses have reported pooled analyses for several cardiometabolic outcomes across a broad range of exercise prescriptions. The majority of evidence supports the benefits of exercise on total cholesterol [ 64 , 71 , 74 , 75 , 121 , 124 , 125 ], potentially driven by benefits on LDL-cholesterol [ 54 , 64 , 65 , 75 , 79 , 82 , 121 , 124 , 125 ]. While one meta-analysis demonstrated within-group benefits for exercise on hepatic insulin sensitivity [ 69 ], the efficacy for improving glycaemic control [ 54 , 65 , 73 , 75 , 79 , 80 ] and the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) [ 25 , 50 , 54 , 59 , 60 , 66 , 67 , 70 , 76 , 123 ] in people with MAFLD is inconsistent.…”
Section: Section 2: Evidence For the Role Of Exercise In The Manageme...mentioning
confidence: 99%
“…It might seem that long-term PA has a distinct and pronounced effect on reducing liver fat content, as measured by MRS or computer tomography scans [ 28 , 123 , 124 ]. Several studies have shown a clear trend towards lower ectopic fat content in the liver after long-term PA, especially in subjects with overweight, obesity, and/or non-alcoholic fatty liver disease [ 125 , 126 ]. It may also seem that plasma free fatty acids, triglycerides, total and low-density cholesterol levels, are lower after long-term PA, probably due to reduced liver fat content, in these individuals [ 125 , 126 ].…”
Section: Effects Of Long-term Pa On Irmentioning
confidence: 99%
“…Several studies have shown a clear trend towards lower ectopic fat content in the liver after long-term PA, especially in subjects with overweight, obesity, and/or non-alcoholic fatty liver disease [ 125 , 126 ]. It may also seem that plasma free fatty acids, triglycerides, total and low-density cholesterol levels, are lower after long-term PA, probably due to reduced liver fat content, in these individuals [ 125 , 126 ]. Furthermore, we have shown that fat content in the liver may be reduced after long-term PA also for normal-weight [ 26 ].…”
Section: Effects Of Long-term Pa On Irmentioning
confidence: 99%